2013
DOI: 10.1002/jid.1710
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of Institutional Quality. More on the Debate

Abstract: 3 ResumenEste trabajo aporta nuevos argumentos sobre los determinantes de la calidad institucional. De forma previa a la exposición del trabajo empírico, se discuten los criterios que deberían valorar la calidad de las instituciones. Posteriormente, se identifican los factores que conforme a estos criterios, determinan la calidad institucional. Los resultados obtenidos en el modelo estimado permiten inferir algunas conclusiones interesantes. La primera, que el nivel de desarrollo determina la calidad instituci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
78
1
13

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(96 citation statements)
references
References 50 publications
4
78
1
13
Order By: Relevance
“…in fact, recent studies have shown it to be a core factor to explain such quality. Alonso and garcimartín (2013) point out that the more educated the population is, the more transparency and dynamic institutions it demands, thus contributing to its own design and development 6 . some previous research -e.g.…”
Section: Theoretical Argumentsmentioning
confidence: 99%
“…in fact, recent studies have shown it to be a core factor to explain such quality. Alonso and garcimartín (2013) point out that the more educated the population is, the more transparency and dynamic institutions it demands, thus contributing to its own design and development 6 . some previous research -e.g.…”
Section: Theoretical Argumentsmentioning
confidence: 99%
“…In another study, Alonso and Garcimartin (2013) pointed towards four attributes of institutional quality, from the perspective of static and dynamic, along with being predictable and credible. Moreover, Siba (2008, p. 10) employed, '"Governance Matters IV" data set constructed by Kaufmann et al (2005)' as a measure of institutional quality.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Openness is indicated in literature to be positively related with enhancing institutional quality (Rodrik et al, 2002;WEO, 2005) . Although Alonso and Garcimartin (2013) did not find the impact of openness to be significant, KOF Index of Globalization, with its multidimensional approach, has been included for checking possible significance.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Both are post-Soviet states that are making the transition from a command economy to a market economy with a similar cultural and institutional legacy of central planning (Alonso and Garcimartin, 2009). At the same time however, these countries are dissimilar in ways that have been deemed important in terms of influencing tax morality.…”
Section: Illegitimate Behaviour Of Entrepreneurs and Institutional Thmentioning
confidence: 99%